Enhancing critical thinking: accounting students' perceptions. Issue 1 (9th January 2017) - Wilkin, Carla L.
Abstract : Purpose: The purpose of this paper is to demonstrate how assessment design was used to enhance students' critical thinking in a subject concerned with business enterprise systems. The study shows positive results and favorable perceptions of the merit of the approach. Design/methodology/approach: A case study approach was used to examine how the problem-based assessment task was redesigned to enhance students' critical thinking. The study documents post-graduate accounting students' achievements, including some comparison with results from an earlier version of the task. Data were collected using surveys and anonymous student comments. Findings: The case study reveals that the merit of the assessment design lay in presenting students with new material that generated some cognitive dissonance, which had to be resolved, rather than just applying subject knowledge to a new scenario. By requiring students to assimilate and harmonize the materials, they were encouraged to think more critically about how their prior learning applied to the problem. Originality/value: Congruent with widespread calls by employers and professional bodies, there is renewed focus on the importance of developing critical thinking skills as an integral part of higher education courses. Whilst achievement is usually realized interdependently through communication, problem solving and analysis, critical thinking must be fostered in the context of the specific professional knowledge. This study contributes knowledge about how students' critical thinking may be fostered, with the added difficulty that the context involves a focus on the role and value of technology.